Ultrasonography for Facial Nerve Palsy: A Systematic Review and Meta-Analysis Protocol - Seojung Ha; Bo-In Kwon; Joo-Hee Kim (MEDrang Inc., 2024)
Background: Facial nerve palsy presents a significant healthcare challenge, impacting daily life and social interactions. This systematic review investigates the potential utility of ultrasonography as a diagnostic tool for facial nerve palsy. Methods: Electronic searches will be conducted across various databases, including MEDLINE, EMBASE, CENTRAL (Cochrane Central register of Controlled Trials), CNKI (China National Knowledge Infrastructure), KMBASE (Korean Medical Database), ScienceON, and OASIS (Oriental Medicine Advanced Searching Integrated System), up to February 2024. The primary outcome will focus on ultrasonography- related parameters, such as facial nerve diameter and muscle thickness. Secondary outcomes will encompass clinical measurements, including facial nerve grading scales and electrodiagnostic studies. the risk of bias in individual study will be assessed using the Cochrane Risk of Bias assessment tool, while the grading of recommendations, assessment, development, and evaluations methodology will be utilized to evaluate the overall quality of evidence. Conclusion: This study aims to review existing evidence and evaluate the diagnostic and prognostic value of ultrasonography for peripheral facial nerve palsy.